An Analysis of Slang Words in Song Lyrics Used in the Songs “That’s What I Like”, “Smoke On The Water”, and “Ch-Check It Out” - Ni Luh Karmila Dewi; Ni Made Ayu Widiastuti (Research and Community Services Institutes of Udayana University, 2020)
The paper entitled “An Analysis of Slang Words in Song Lyrics Used in the Songs “That’s What I Like”, “Smoke On The Water”, and “Ch-Check It Out”. This study concern with the analysis of slang words in the Songs “That’s What I Like”, “Smoke On The Water”, and “Ch-Check It Out”. There are three statement problems (1) What are the types of slang words used in the song? (2) What is the meaning of slang words in the three sample that are in the lyric? (3) What is dominant type of slang words of three song lyrics? The data of this study were collected from three song lyrics in different genres: pop, rock, and rap song. Documentation method was used to collect the data and qualitative method was used to describe the types of slang words, the meaning of slang word, and dominant types of slang words that used in three song lyrics. The writer used theory of the types slang by Patridge (2004:204) and the meaning of the slang word used theory by Geoffrey Leech (1974).There are six types of slang words which are found in this study such as four slang words in publicity, four slang in public School and University, twenty one slang words in society, three slang in theatre, one soldier’s slang, and one public house slang. Then, there are six meanings of slang word are found by the writer: seven in collocative meaning, six in conceptual meaning, five in stylistic meaning, three in connotative meaning, six in reflected meaning and four in affective meaning. From the analysis that were found that society slang and collocative meaning mostly found and used in there song lyrics.